Implikasi Pola Asuh Anak dalam Keluarga Mualaf Terhadap Praktek Ibadah di Yayasan Mualaf Center - Saleh Salihin; Mukhsin Nyak Umar; Masbur Masbur (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
This article aims to 1) find out what parenting patterns are applied in the family of converts in fostering the practice of worship in children at the Mualaf Center Foundation, Subulussalam City. 2) what are the obstacles of the converts family in fostering children's worship practices at the Mualaf Center Foundation in Subulussalam City This research uses field research with a qualitative approach, the instruments used are interviews and documentation The Mualaf Foundation of the Mualaf Center of Subulussalam City has conducted routine studies in fortifying Aqidah and deepening religious knowledge every two times a week, In this process, parents have done their best to teach their children to provide religious understanding, some teach their own children and some give it to the Koran teacher/ustadpola parenting of converts in increasing understanding of the values of worship at the Mualaf Center Foundation in Subulussalam City in the families of converts is different, some are successful and some are not successful. The obstacle that muallaf families face is the lack of knowledge about Islamic teachings so that it is difficult to apply parenting patterns for children to understand the values of worship according to Islamic teachings.